2016
DOI: 10.12688/f1000research.8221.1
|View full text |Cite
|
Sign up to set email alerts
|

Members of the genus Burkholderia: good and bad guys

Abstract: In the 1990s several biocontrol agents on that contained Burkholderia strains were registered by the United States Environmental Protection Agency (EPA). After risk assessment these products were withdrawn from the market and a moratorium was placed on the registration of Burkholderia-containing products, as these strains may pose a risk to human health. However, over the past few years the number of novel Burkholderia species that exhibit plant-beneficial properties and are normally not isolated from infected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
196
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 255 publications
(207 citation statements)
references
References 95 publications
4
196
0
7
Order By: Relevance
“…However, Eberl and Vandamme [20] criticized the lack of several type strains in the study by Sawana et al [16] and noted that the authors ignored phylogenetic heterogeneity, as revealed by 16S rRNA gene-based divergence and by differences in the distribution of 22 additional conserved sequence indels, in their simplistic inclusion of all species outside Clade I (Burkholderia sensu stricto) within the novel genus Paraburkholderia. According to this scheme, the deep-branching lineages of B. rhizoxinica, B. endofungorum, B. caryophylli, B. symbiotica, B. soli and B. andropogonis are all to be included within Paraburkholderia.…”
Section: Minute 10 Agrobacteriummentioning
confidence: 99%
See 1 more Smart Citation
“…However, Eberl and Vandamme [20] criticized the lack of several type strains in the study by Sawana et al [16] and noted that the authors ignored phylogenetic heterogeneity, as revealed by 16S rRNA gene-based divergence and by differences in the distribution of 22 additional conserved sequence indels, in their simplistic inclusion of all species outside Clade I (Burkholderia sensu stricto) within the novel genus Paraburkholderia. According to this scheme, the deep-branching lineages of B. rhizoxinica, B. endofungorum, B. caryophylli, B. symbiotica, B. soli and B. andropogonis are all to be included within Paraburkholderia.…”
Section: Minute 10 Agrobacteriummentioning
confidence: 99%
“…Notwithstanding that there are valid taxonomic reasons for splitting Burkholderia sensu lato into several genera, the members of this group cannot be described as pathogens or non-pathogens solely on the basis of their affiliation to a particular clade [20]. However, many strains, particularly rhizobial and plant beneficial strains from Clade III, show great potential as biofertilizers and bioremediants in sustainable agricultural systems.…”
Section: Minute 10 Agrobacteriummentioning
confidence: 99%
“…On the basis of a PGPR screening assay, 47% of the isolates were able to produce IAA, 58.8% could solubilize phosphate, none produced HCN and 100% produced siderophores. Isolate SYP31 was able to produce IAA in the media without tryptophan addition, while other isolates did not produce IAA in the media without tryptophan (Table 4 a large number of commercially hydrolytic enzymes and bioactive substances which are beneficial for plant growth and health (Eberl and Vandamme 2016). B. cepacia is a ubiquitous soil organism which has been effectively used as a biocontrol agent against many plant pathogenic fungi such as Colletotrichum gloeosporioides (de Los Santos-Villalobos et al 2012), Pythium-induced dampingoff, Aphanomyces-induced root rot of pea, Rhizoctoniainduced root rot of Poinsettia and other fungal diseases (Parke et al 1991;King and Parke 1993;Cartwright and Benson 1994;Fridlender et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…B. cepacia is a ubiquitous soil organism which has been effectively used as a biocontrol agent against many plant pathogenic fungi such as Colletotrichum gloeosporioides (de Los Santos-Villalobos et al 2012), Pythium-induced dampingoff, Aphanomyces-induced root rot of pea, Rhizoctoniainduced root rot of Poinsettia and other fungal diseases (Parke et al 1991;King and Parke 1993;Cartwright and Benson 1994;Fridlender et al 1993). In the USA, several strains of B. cepacia have been registered by The United States Enviromental Protection Agency (EPA) as biocontrol agents against plant pathogenic fungi (Eberl and Vandamme 2016;Rai 2006). The ability of B. cepacia to act as a biocontrol agent is due to its production of various compounds with antifungal activity (Vial et al phosphate and zinc, sequestration of iron by siderophore production, production of phytohormones such as Auxins, cytokinins and gibberellins, production of the enzyme 1-aminocyclopropane-1-carboxylate (ACC) deaminase promote direct plant growth.…”
Section: Discussionmentioning
confidence: 99%
“…The complex is of both medical and biotechnological importance, medical because of the strains' ability to cause infections in cystic fibrosis and immunocompromised patients, and biotechnological due to their plant growth-promoting and biocontrol capabilities (5). The environment is known to be a source of Bcc acquisition (6,7), which has prevented the realization of the agricultural potential of these bacteria (8). The Bcc genome is large (nearly 8 Mb for Burkholderia cenocepacia H111) and consists of at least three replicons; these are chromosomes 1 and 2 and the megaplasmid pC3.…”
mentioning
confidence: 99%